Pharmaceutical care in general medical ward at middle-level Hospital - กิจไพบูลย์ทวี, ศศิธร (Region 11 Medical Journal, 2017)
Objective : Of this study was to identify types and frequencies of drug-related problems (DRPs) found during hospitalization in general medical ward, Sichon hospital, during April 1, 2015 – March 31, 2016. It was a prospective descriptive study. The ward pharmacist reviewed the medical chart by focusing on patients’ data, drug used and administration and potential adverse drug reaction; medication reconciliation, interview and counseling patients and/or caregiver. If any DRPs were detected, ward pharmacist would coordinated with health care team, patient and/or caregiver for preventing, solving or monitoring. All of DRPs were classified and scored for their potential clinical impact by ward pharmacist. Results : Showed that ward pharmacist had observed 440 DRPs in 345 patients (15.5% of 2,225 patients). The most frequent DRPs was untreated indications (33.2%), followed by improper drug selection (21.8%) and drug use without indication (10.9%), 92.3% of DRPs could be prevent or solve by ward pharmacist. The majority of potential clinical impact score of pharmacist intervention was significance (38.4%). Pharmacists’ recommendations were received with high acceptance (93.2%) The results of this study was an opportunity for improve the medication management system for efficacy and quality care and treatment outcome though the medication safety in hospital